Tax Structures and Economic Growth: New Evidence from the Government Revenue Dataset. (13th March 2018) - McNabb, Kyle
Abstract: This study uses the ICTD UNU‐WIDER Government Revenue Dataset in order to challenge and extend existing findings on the relationship between tax structures and economic growth, in a panel of 100 countries. The results suggest that, broadly, revenue‐neutral increases in income taxes are associated with lower long‐run GDP growth and that revenue‐neutral reductions in trade taxes have not always had positive effects. Crucially, many of the results presented differ according to income level, calling into question the validity of existing findings for developing countries and suggesting that policy advice on this issue in developing countries should be viewed through a more cautious lens. © 2018 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.